The Effect of Shopee Social Media Marketing on Purchasing Decisions at Borneo Store Banjarmasin (Case Study of Purchasing an Iphone Online) - Suarniki, Ni Nyoman; Apriana, Rizky Amalia; Kamila, Azkia; Agustina, Ruslinda; Gustiana, Rara (MSJ : Majority Science Journal, 2024)
The purpose of this study was to determine Shopee's social media marketing influence on purchasing decisions at the Borneo Store. The research method used is quantitative descriptive method. The population of this study were buyers at Borneo Store. The sample was 20 respondents. Multiple linear regression data analysis techniques with the SPSS version 22 program. The results showed that the influence of Content Creation (X1) had a partially significant positive effect on purchases (Y) as evidenced by the t value of 2.509> t table 2.014 and the significance value (Sig.) 0.002 <0.050, which means that the Content Creation variable (X1) has a partial and significant effect or a positive effect on Purchasing Decisions. The test results show that the effect of Content Sharing (X2) has a partially negative significant effect on purchases (Y) as evidenced by the t value of 1.643 < t table 2.014 and the significance value (Sig.) 0.095> 0.050, which means that the Content Sharing variable (X2) has no partial and insignificant effect or negative effect on Purchasing Decisions.The test results show that the effect of Connecting (X3) has a partially positive significant effect on purchases (Y) as evidenced by the t value of 2.529> t table 2.014 and the significance value (Sig.) 0.015 <0.050, which means that the Connecting variable (X3) has a partial and significant effect or a positive effect on purchasing decisions. The test results show that the effect of Community Building (X4) has a partially negative significant effect on purchases (Y) as evidenced by the t value of 1.865 < t table 2.014 and the significance value (Sig.) 0.069 > 0.050, which means that the Community Building variable (X4) has no partial and insignificant effect or negative effect on Purchasing Decisions. The results showed that the Content Creation, Content Sharing, Connecting and Community Building variables on the Borneo Store Purchasing Decision assumed that the Content Creation (X1), Content Sharing (X2), Connecting (X3) and Community Building (X4) variables jointly influenced the Purchasing Decision (Y). The results of the simultaneous test show the calculated F value of 2.47 with a significance value of 0.000 <0.050.